Interconnections between governance and socioeconomic conditions: Understanding Sub-Saharan African challenges - Fisayo Fagbemi; Geraldine E. Nzeribe; Tolulope Temilola Osinubi; Simplice Asongu (African Governance and Development Institute (AGDI), 2021)
Given that challenges facing sub-Saharan African (SSA) countries on the issue of socioeconomic development have been identified as critical to strengthening the inherent link between governance and socioeconomic conditions, this study examines the interconnections between governance and SSA socioeconomic conditions. With a focus on 25 countries between 2005 and 2019, the analysis is based on Panel-Corrected Standard Error (PCSE) and System-GMM estimations, and panel causality test.Results show that SSA seems not to have the means of effective governance to spur improved socioeconomic conditions. Findings indicate that the pervasiveness of institutional problems in many SSA countries has been responsible for the poor socioeconomic condition in the region.Furthermore, it is equally found that governance quality and socioeconomic conditions are mutually reinforcing, suggesting that they influence each other. An improvement in socioeconomic conditions could result in better governance. On the other hand, the quality of governance is viewed as a vital ingredient in achieving needed socioeconomic development outcomes. Thus, it is suggested that there is need for SSA countries to streamline governing system towards engendering improved well-being. The introduction and implementation of transformative policies through effective governance are also necessary for ensuring critical structural changes and increased social service provision. Overall, there should be a proactive identification of ineffective policies and procedures by policymakers to enhance meaningful impact in the region.
Keywords: 330; Governance quality; socioeconomic condition; economic development; SystemGMM; Africa